Motivating Factors on Choosing Perth as the Choice Tourism Destination for Education - Wiraharja, I Putu Gede Satria (Journal of Business on Hospitality and Tourism, 2023)
Motivation is the driving force that ensures the continuity of learning activities and provides direction for learning activities so that the desired goals can be fulfilled. Thus, motivation is very influential on one's learning outcomes. If someone does not have the motivation to learn, then that person will not achieve optimal learning results. The purpose of this study is to analyze how much motivation international students have in choosing Perth as a tourist destination for education. This study uses a survey method. Primary data collection was conducted by interviewing fifteen international students. All respondents answered ten closed questions. Data collected through questionnaires were analyzed qualitatively. The results of this survey state that Australia is one of the most popular countries so that Australia is one of the most visited countries from various parts of the world, especially to learn English and even to continue to a higher level of education. This is because Australia is the safest country, has a comfortable atmosphere, friendly people, and has a good transportation system that makes it easier for people to travel between states.